Student Perceptions of the Effectiveness of Government Public Service Applications in the Digital Era - Laela Worotikan; Wahid Ahmad Tiar Idris; Fredrik Alven Kalendi; Gabriela Yoshephine Henriette Pantou; Moh. Afdal S. Rahman (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Background: Digital transformation has become a fundamental component of public service improvement in the era of rapid technological advancement. The Indonesian government continues to introduce and refine digital platforms intended to provide more efficient, transparent, and accessible public services to citizens across all demographic groups. Objective: This study aims to explore student perceptions regarding the effectiveness of government digital public service applications, identify the benefits experienced by student users, and analyze the challenges that hinder optimal service delivery. *Methods: This research employs a qualitative descriptive design with a phenomenological approach to understand the lived experiences of students who utilize digital government applications. Data were collected through observation and in-depth descriptive narration from students who actively use various government digital platforms including population administration systems (Dukcapil Online), health services (Mobile JKN), educational financial assistance (KIP Kuliah), and public complaint systems (SP4N-LAPOR!). Thematic analysis was applied to identify patterns in user experiences across multiple service dimensions.* Results: Findings reveal that students generally view these applications positively, citing ease of access, time efficiency, reduced administrative costs, and increased transparency as major advantages over traditional bureaucratic processes. However, persistent challenges remain including system instability during peak usage periods, high mobile data consumption, unclear instructions and interface designs, insufficient accessibility features for users with disabilities, and concerns about personal data security and privacy. These challenges demonstrate the need for further refinement in technical infrastructure, user-centered design, and stronger digital governance practices.